Learning from Failures: Architectures of Emergency in Contested Spaces (Pyla, Cyprus) - Socrates Stratis (Footprint)
One of the characteristics of contested spaces of ethno-religious origin is the failure to work around common projects. This is the case of the community of Pyla, Cyprus, one of a few inter-ethnic communities on the island. Architectural and planning practices are urged to contribute to the process of reconciliation, despite the lack of an on-going official reconciliation process, and their lack of power.